ABDOMINAL VAGINAL SURGERY IN THE TREATMENT OF URINARY INCONTINENCE DISTOPIA EFFORT ASSOCIATED WITH PELVIC - Ludmir, A. (2015)
ystopia in the San Bartolome Hospital, from June 1971 to December 1977. The 98% of patients were over 35 years of age is presented; 60% were large multiparous and an additional 36% had parity between 3 and 6. Almost 60% of cases had a median incontinence efforts. 90% of cases presented a cystocele 11-111 and there was a 8.77% of uterine prolapse. The surgical technique used was mixed, practiced anteroposterior colporrhaphy, urethroplasty Kelly-Ball and Marshall-Marchetti-Krantz; the uterus was removed vaginally in 64 cases and abdominal approach in 169 cases. One 32.69% of post operative morbidity was observed, with most cases of infection dependent. There were two Vesicouterine fistulas. Recurrences in the 248 cases that could be evaluated in four years, was around 6.8%. The lowest recurrence rate was observed precisely in cases where Kelly-Ball urethroplasty was done in conjunction with the Marshall-Marchetti-Krantz. The removal of the uterus does not seem to change the postoperative prognosis of incontinence.